ESTIMATING OF HETEROSIS AND GENETIC VARIABILITY IN SUMMER SQUASH( Cucurbita pepo L.) - Shamil Y.Hassan Al-Hamdany (Mesopotamia Journal of Agriculture)
This study was carried out in the vegetable field of Department of Horticulture and land Scape Design, College of Agriculture and forestry/ Mosul University, during spring and autumn seasons 2007 ,by using a randomized complete block design with three replications .The aim of the study was to evaluate four parents and their hybrids to estimate heterosis , genetic variability and heritability for the studied traits by full diallel crosses of four summer squash varieties : 1 Local , 2 Syrian , 3 Tala &4 Bather Elbethor. The results of statistical analysis showed that there was significant differences among the parents and their hybrids for all the studied characters. The parent Tala (3) was higher than for early and total yield, while the hybrid 2×3 gave highest value for early yield and the hybrid 2×4 for total yield. All the hybrids exhibited significant heterosis for all the studied characters whete the hybrid 4×1 had the highest positive significant value for plant length the hybrid 3×1 fruit length and the hybrid 2×3 for fruit weight, while the hybrid 4×2 showed superiority for fruit number and early yield, and the hybrid 2×4 for total yield. The results also showed that narrow sense heritability was in the range of medium to high for plant height, number of leaves/ plant, male flowering date, fruit length and width and number of fruits / plant. Average degree of dominance was greater that one for all the characters except for plant length, indicating that over dominance control the inheritance of these characters.